(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Bilingualism, the proficiency in two or more languages, is a widespread occurrence shaped by historical, social, and cultural influences. However, when viewed through the perspective of cultural imperialism, it becomes a nuanced issue. The predominance of one language over others can contribute to the decline of minority languages, establishing a cultural hierarchy where one language and its culture are prioritized.